Por práticas pedagógicas diferenciadas no ensino de Ciências no contexto da educação do campo, Senador José Porfírio, Pará - BARBOSA, Helena Géssica Nascimento (2023)
The objective is to discuss the use of different methodologies in Science teaching in the context of rural schools in the municipality of Senador José Porfírio. Rural Education, referring to the final years of elementary school, held at Escola Rosa Alvarez Rebelo. This pole school located in the municipality's headquarters receives students who live in the surrounding peasant communities, in the regions of roads and rivers. However, the use of differentiated methodologies referenced in the different social identities of the students was not verified. The principles of rural education, constructionist pedagogical currents and innovative strategies stand out for autonomy and for the theory-practice relationship. In this sense, practical activities and the inclusion of communities in the educational process are central elements for the construction of differentiated methodologies.